An investigation of inkjet printing of polycaprolactone based inks - He, Yinfeng (2016)
Traditional manufacturing methods like moulding or subtractive manufacturing place significant limitations on structures which could be manufactured in a single process. These limitations can now be overcome by a new manufacturing technology—Additive Manufacturing (AM), which provides the users much more freedom to design and produce structures in one piece. Additive manufacturing refers to a range of processing technologies, which fabricate 3D parts by adding successive layers. With this technology, complex 3D structures can be produced directly following the production of a geometric data. Additive manufacturing also enables production without the need of tooling, which brings the prospect of a revolution in the manufacturing industry.